2016
DOI: 10.1007/s11010-016-2840-9
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte genotoxicity and protective effect of Calyptranthes tricona (Myrtaceae) against H2O2-induced cell death in MCF-7 cells

Abstract: Calyptranthes tricona is a species (Myrtaceae) native to South Brazil. Plants belonging to this family are folkloric used for analgesia, inflammation, and infectious diseases. However, little is known about the toxic potential of C. tricona. The present study aimed to evaluate the antioxidant activity of C. tricona ethanol and hexane leaf extracts, as well as verify their effect on human lymphocytes and MCF-7 cells. The extracts were subjected to preliminary phytochemical screening, antioxidant activity using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Hydrogen peroxide is a major factor implicated in the free-radical theory of aging. Many reports have proved that H 2 O 2 can trigger oxidative damage and cell death in different types of cells, such as H9c2 cardiomyoblasts, MCF-7 breast adenocarcinoma cells, and retinal cells. Oxidative damage should be restricted by the intervention of efficient antioxidant-defense mechanisms, but ROS levels increase, and antioxidant levels decrease in aging tissues . Here, H 2 O 2 was used to induce oxidative stress in the human retinal pigment epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide is a major factor implicated in the free-radical theory of aging. Many reports have proved that H 2 O 2 can trigger oxidative damage and cell death in different types of cells, such as H9c2 cardiomyoblasts, MCF-7 breast adenocarcinoma cells, and retinal cells. Oxidative damage should be restricted by the intervention of efficient antioxidant-defense mechanisms, but ROS levels increase, and antioxidant levels decrease in aging tissues . Here, H 2 O 2 was used to induce oxidative stress in the human retinal pigment epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…7c). This result illustrated that the programmed cell death of MCF-7 cells caused by H 2 O 2 treatment [24,25]. However, a remarkable decrease in the number of apoptotic MCF-7 cells was observed when MCF-7 cells were treated with PCB 2 (0.1-10.0 µM).…”
Section: Discussionmentioning
confidence: 78%
“…In the study of Saverini et al () α‐pinene and β‐pinene demonstrated genotoxic effect with comet assay. Many plants were evaluated with comet assay for genotoxicity assessment in previous studies (Cho et al, ; Etebari et al, ; Ferrer et al, ; Gafrikova et al, ; Kich et al, ; Llana‐Ruiz‐Cabello et al, ), but, so far, no study has evaluated genotoxicity of H. persicum . Mutations are initial stages in carcinogenesis, therefore, a short term bacterial test, such as the Salmonella /microsomal assay or Ames test has been utilized for the finding of mutagens (Boubaker et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that terpenes such as α-pinene can increase the malondialdehyde (MDA) levels and γ-terpinene significantly induced DNA damage in human lymphocytes (Aydin, Basaran, & Basaran, 2005). In the study of Saverini Etebari et al, 2012;Ferrer et al, 2014;Gafrikova et al, 2014;Kich et al, 2017;Llana-Ruiz-Cabello et al, 2016), but, so far, no study has evaluated genotoxicity of H. persicum. Mutations are initial stages in carcinogenesis, therefore, a short term bacterial test, such as the Salmonella/microsomal assay or Ames test has been utilized for the finding of mutagens (Boubaker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%